PENGARUH PERCEIVED WAITING TIME DAN SATISFACTION WITH WAITING ENVIRONMENT TERHADAP SERVICE SATISFACTION DI RESTORAN XSURABAYA - Bian Pagudisaputra; Siti Rahayu; Fitri Novika Widjaja (CALYPTRA, 2018)
This research was conducted to determine the effect of perceived waiting time andsatisfaction with waiting environment on waiting time satisfaction and service satisfaction in X restaurant Surabaya. Descriptive analysis along with Partial Least Square is used in this research. The result shows there is a positive significant effect between perceived waiting time and waiting time satisfaction also from waiting time satisfaction and service satisfaction, and also a positive but not significant effect from satisfaction with waiting environment and waiting time satisfaction also from satisfaction with waiting environment and service satisfaction. It also found a negative but not significant effect from perceived waiting time and service satisfaction.